Global Economic Inequality: A Critical Analysis of the Contribution of Islamic Economic Principles as an Alternative Solution - Muhammad Syahrul Hidayat; Dede Nurohman (STAIN Bengkalis, 2023)
This study explores the contribution of Islamic economic principles as an alternative solution to global economic inequality. Through a literature review and critical analysis of related literature, this study found that Islamic economic principles, such as social justice, equitable distribution of wealth, and prohibition of usury, have the potential to reduce such inequality. However, challenges such as lack of understanding and awareness, inconsistent implementation, and regulatory barriers need to be overcome. Strategic measures are needed, including more widespread Islamic economic education, strong policy support, and collaboration between the government, financial institutions, and society. This research contributes to strengthening the understanding of the role of Islamic economics in addressing global economic inequality, with the hope of achieving more equitable and sustainable economic prosperity around the world.